2018
DOI: 10.1002/anie.201800767
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Promoted Dearomative Fluoroalkylation of β‐Naphthols through Intermolecular Charge Transfer

Abstract: The first visible-light-promoted dearomative fluoroalkylation of β-naphthols was realized without the assistance of any transition-metal catalysts or external photosensitizers. Inexpensive fluoroalkyl iodides were directly used as efficient fluoroalkylation reagents under very mild reaction conditions. The scope of this process was found to be general and broad, and both trifluoromethyl and perfluoroalkyl groups (-C F , -C F , and -C F ) were installed in excellent yields. Preliminary mechanistic studies sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(46 citation statements)
references
References 109 publications
0
46
0
Order By: Relevance
“…Xu and colleagues have accomplished the visible‐light promoted dearomatizative fluoroalkylation of β‐naphthols in the absence of photocatalysts. The protocol represents an advantageous synthesis, as the known perfluoroalkylation strategies of naphthols always led to O ‐fluoroalkylation.…”
Section: Visible Light Photoactive Eda Complexes Involving Rf–i Anmentioning
confidence: 99%
“…Xu and colleagues have accomplished the visible‐light promoted dearomatizative fluoroalkylation of β‐naphthols in the absence of photocatalysts. The protocol represents an advantageous synthesis, as the known perfluoroalkylation strategies of naphthols always led to O ‐fluoroalkylation.…”
Section: Visible Light Photoactive Eda Complexes Involving Rf–i Anmentioning
confidence: 99%
“…[1] Visible-light photoredox catalysis has been proven to be ap owerful and environmentally friendly tool to initiate av ariety of organic reactions. [6] Most recently,t he group of Melchiorre and others developed avisible-light-induced organic reaction that relied on the formation of either an electron donor-acceptor (EDA) complex [7,8] or excited state of organocatalytic intermediates, [2e, 9] which enabled radical transformations to develop under photocatalyst-free conditions (Scheme 1a). [6] Most recently,t he group of Melchiorre and others developed avisible-light-induced organic reaction that relied on the formation of either an electron donor-acceptor (EDA) complex [7,8] or excited state of organocatalytic intermediates, [2e, 9] which enabled radical transformations to develop under photocatalyst-free conditions (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…[2] However,b ecause of the weak interaction of simple organic molecules with visible light, most synthetic strategies rely upon the use of photoredox catalysts (PCs), such as Ru-complexes, [3] Ircomplexes, [4] organic dyes, [5] as well as other photosensitizers. [6] Most recently,t he group of Melchiorre and others developed avisible-light-induced organic reaction that relied on the formation of either an electron donor-acceptor (EDA) complex [7,8] or excited state of organocatalytic intermediates, [2e, 9] which enabled radical transformations to develop under photocatalyst-free conditions (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, transition metal catalysts such as Ir and Ru complexes( III-VI)w ere also tested, and none of them gave improved results. In these cases, the competitive side reactionb etween b-naphthols and singlet oxygen was observed (entries [8][9][10][11]. [7] Finally,c ontrol experiments confirmed that photocatalyst, visible light and air were essential for this reaction (entries12-14).…”
mentioning
confidence: 97%
“…[6] Despite this blooming of photo-chemistry,t he utilization of visible-light-mediated photoredox catalysis in intermoleculard earomatization of naphthols remainsl argely underexplored. [7,8] Given the merits of visible-light-mediated photoredox catalysis and our continuing interest towards dearomatization reactions,w eb egan to explore oxidative dearomatization of naphthols under visible-light-mediated photoredoxc atalysis. We envisaged the catalystc onverting naphthols into radical cation intermediates, which might then be trapped by intriguing nucleophiles such as N-hydroxycarbamates, to forge the fully substituted stereogenic center.…”
mentioning
confidence: 99%